A Mathematical Transition Course Revisited: An Adelphi University Case Study. Issue 6 (3rd July 2021) - Petrilli, Salvatore J.
Abstract : The Department of Mathematics and Computer Science at Adelphi University engaged in a year-long program revision of its mathematics major, which was initiated by a longitudinal study and the publication of the 2015 Curriculum Guide by the MAA's Committee on Undergraduate Programs in Mathematics. This paper stands as a short story, so to speak, of a mathematics department's reflection, assessment, and replacement of its 2006 transition to higher mathematics course. The paper ends with some conclusions and recommendations that the Author hopes will spark conversations within the mathematics and mathematics education communities.